Optimasi Data dengan Regresi Linier pada Klasifikasi Potensi Kenaikan CFR Demam Berdarah - Anik Andriani - UBSI (SPEED - Sentra Penelitian Engineering dan Edukasi, 2020)
ABSTRACT - The main problem of data collection is the finding of irregular and unstructured data. That is why we often find much data missing value while collecting them. The result of classification is affected by the data quality. Linear Regression is one of methods in Machine Learning that we can use it to estimate the value of data based on the correlation between variables in the dataset. We can also use the method to estimate the missing values in a dataset, so it will optimize te dataset to be used for classification. To examine the performance of the linear regression method in estimating missing values that carried out in the Case Fatality Rate dataset Dengue Fever in Indonesia, is to classify whether there is a potential increase in the percentage of Dengue fever Fatality Rate Cases in a province. The classification is done two times; first it using a dataset without missing value, and the second using a dataset with optimal data after the estimated missing value. The classification is carried out on the training data, while to determine its performance, it uses the results of the classification test on the testing data. The results show the classification of data both in training data and testing data using an optimized dataset has a higher percentage of accuracy than the dataset that removes missing value data.Keywords: Missing Value, Linear Regression, Classification, Case Fatality Rate, Dengue FeverABSTRAK - Permasalahan utama pada pengumpulan data adalah data tidak teratur dan tidak terstruktur.  Seringkali kita mengumpulkan data dengan banyaknya data missing value di dalamnya.  Hasil klasifikasi sendiri sangat terpengaruh pada kualitas dari data.  Regresi Linier merupakan salah satu metode dalam Machine Learning  yang dapat digunakan untuk memperkirakan nilai dari suatu data berdasarkan korelasi antar variabel dalam dataset.  Teknik ini dapat digunakan untuk memperkirakan nilai yang hilang dalam dataset sehingga dapat mengoptimalkan dataset yang akan digunakan untuk klasifikasi.  Untuk menguji performa metode regresi linier dalam memperkirakan missing value dilakukan  pada dataset Case Fatality Rate penyakit Demam Berdarah di Indonesia untuk mengklasifikasi apakah ada potensi kenaikan presentase Case Fatality Rate Demam Berdarah di suatu provinsi atau tidak.  Klasifikasi dilakukan dua kali yaitu pertama menggunakan dataset tanpa missing value dan kedua menggunakan dataset dengan data optimal setelah diperkirakan nilai missing value.  Klasifikasi tersebut dilakukan pada data training, sedangkan untuk mengetahui performanya dilakukan pengujian hasil klasifikasi pada data testing.  Hasilnya menunjukkan klasifikasi data baik pada data training maupun data testing menggunakan dataset yang sudah dioptimasi memiliki presentase akurasi yang lebih tinggi dibanding dataset yang membuang data missing value.Keywords: Missing Value, Linear Regression, Classification, Case Fatality Rate, Demam Berdarah